2015
DOI: 10.4049/jimmunol.1501153
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hepcidins in a Teleost Fish, Dicentrarchus labrax: Different Hepcidins for Different Roles

Abstract: Teleost fish rely heavily on their innate immunity for an adequate response against pathogens and environmental challenges, with the production of antimicrobial peptides being one of their first lines of defense. Among those is hepcidin, a small cysteine-rich antimicrobial peptide that is also the key regulator of iron metabolism. Although most mammals possess a single hepcidin gene, with a dual role in both iron metabolism regulation and antimicrobial response, many teleost fish present multiple copies of hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 71 publications
9
82
0
Order By: Relevance
“…In teleost fish, innate immunity is also the first line of defense against pathogens (68). Although the adaptive immunity of teleosts is weak, they possess more diverse innate immune molecules than do mammals (34,69). Macrophage dysfunction is related to the survival of septic mice and teleost fish (38,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In teleost fish, innate immunity is also the first line of defense against pathogens (68). Although the adaptive immunity of teleosts is weak, they possess more diverse innate immune molecules than do mammals (34,69). Macrophage dysfunction is related to the survival of septic mice and teleost fish (38,43).…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrate evolution, gene duplications produce redundant genes, which are associated with adaptive radiations in teleosts (32,33). These redundant genes may result in subfunctionalization, as in the case of sea bass (Dicentrarchus labrax), in which different hepcidins exhibit different roles (34). In this study, we found that CXCR3.1 and CXCR3.2 were expressed in the macrophages of the teleosts: ayu (Plecoglossus altivelis), grass carp (Ctenopharyngodon idella), and spotted green pufferfish (Tetraodon nigroviridis).…”
mentioning
confidence: 99%
“…Studies in fish species of Hep protein have shown multiple isoforms exist and these are classified into two groups: Hamp type and Hamp type 2. One Hep isoform has iron regulatory roles sharing a high degree of homology with mammalian counterparts, and the second Hep copy has retained only the antimicrobial role [9,49]. Phylogenetic analysis in this study has shown the isoform identified in meagre is more similar to Hamp 2 and likely does not retain the iron regulatory functions.…”
Section: Discussionmentioning
confidence: 74%
“…Fish have developed several defense mechanisms against waterborne pathogens with one of the first lines of defense consisting relatively small peptides called antimicrobial peptides (AMPs) (Neves et al 2015). Antimicrobial peptides are identified as a positively charged molecules with short amino acid chains which play crucial roles in host defense against pathogens through antimicrobial actions or immunomodulatory functions (Jenssen et al 2006).…”
Section: Introductionmentioning
confidence: 99%